Biostratigraphic characterization of the Jurassic deposits of the Flat Crimea and the Near-Sivash region - Matlaj, L.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The biostratigraphic description of the Jurassic deposits of the Flat Crimea and the Near-Sivash region for mollusks, foraminifera, calcareous nannoplankton, spores, and pollen is given. For the first time, the associations of calcareous nannoplankton for the Lower Bajocian and Aptian wells of Shubinskaya-7 have been identified. The regional stratigraphic scheme of the Jurassic deposits of the Flat Crimea and the Prisivashija region is made.